Ceramic raptors unearthed at the site of Shimao (2300–1800 BCE) in northern China: Production and use. (April 2023) - He, Limin; Yao, Shuai; Sun, Zhouyong; Shao, Jing; Di, Nan; Li, Tao
Graphical abstract: Highlights: Over 1200 ceramic raptor fragments were unearthed at Shimao. They were largely similar to utilitarian pottery in chemical composition. Different producers likely produced three subgroups of ceramic raptors. Production and context of use were discussed on ceramic raptors. Ceramic raptors were part of the political landscape created by Shimao elites. Abstract: Ceramic raptors were unearthed at the site of Shimao (2300–1800 BCE), a 425-ha walled settlement on the Loess Plateau in northern Shaanxi, China. Bird-shaped figures of similar size and age are rare in prehistoric East Asia. For the first time, the present paper conducted a compositional study on the Shimao ceramic raptors using a non-invasive handheld X-ray fluorescence (hhXRF) analyzer. The hhXRF data were compared with those of Shimao utilitarian vessels and local clays to investigate the production of these artifacts. Multivariate statistical analyses of the compositional data suggest that the ceramic raptors are primarily similar to utilitarian pottery in chemical composition but the source(s) of the clay for making them do not match those of the sampled soils. Three subgroups of the ceramic raptors are recognizable by their body color and characteristics of the exterior surface, and they demonstrate compositional variability possibly suggesting different sources of the clay. In addition, calcium-rich whitish substances are inferred as residues of a white paint intentionally applied during the production or use of ceramic raptors. Based on a discussion of archaeometric and archaeological evidence, we propose that the Shimao ceramic raptors were manufactured by multiple production units and meant to mimic a specific, culturally significant bird species (eagles). We also speculate that they were displayed during special events at restricted locales and were intentionally (even ritually) discarded after use. It is possible that the ceramic raptors constituted a part of the political landscape shaped by the Shimao elites, who possessed authority and power on a regional scale.